Anti-Mullerian Hormone and conception timing as predictors of live births in cancer patients using fertility preservation: a systematic review - Klonoff-Cohen, Hillary; Polavarapu, Mounika; Ramachandran, Neha (Frontiers in Oncology, 2025)
ObjectivesAmong women of childbearing potential aged 15–39, cancer incidence is 52.3 per 100,000 annually. Women newly diagnosed with cancer often have just 2–6 weeks to decide whether to pursue fertility preservation (FP) before commencing treatment. The recommended waiting period to conceive post-treatment ranges from 6 months to 5 years, depending on cancer type, treatment, and age. With >18 million young adult cancer survivors worldwide, identifying factors affecting fertility preservation and live birth outcomes is more critical than ever. This is the first systematic review to explore whether AMH levels before, during, or after chemotherapy predict pregnancy outcomes resulting from re-utilization of stored oocytes/embryos or spontaneous conception in cancer patients undergoing FP. It also evaluates the optimal timing for post-treatment AMH recovery and how this may inform fertility success and decision-making for cancer patients pursuing FP.MethodsA review of PubMed and Web of Science identified 458 studies until November 2024. After a full-text review of 38 studies, seven met the eligibility criteria: if they were peer-reviewed, in English, enrolled female cancer patients undergoing FP before chemotherapy, measured AMH, and reported pregnancy or live birth rates after chemotherapy. Study quality and relevance were categorized as high, moderate, or low. Of the seven studies, one was highly relevant, four were moderately relevant, and two were of lower relevance.ResultsThe majority of studies focused on patients with breast cancer or lymphoma, comprising three prospective and four retrospective designs. Oocyte cryopreservation emerged as the most commonly used fertility preservation method. Among those who used stored specimens, baseline AMH levels ranging from ~2.1 to 2.8 ng/mL were related to live birth rates of 35–42%. Notably, spontaneous conception was more frequent than assisted reproduction. AMH recovery timelines varied widely, with follow-up periods spanning 1 to 36 months, yet no clear optimal timeframe for ovarian reserve restoration emerged.ConclusionIn female cancer patients, pre-treatment Anti-Müllerian Hormone (AMH) levels may offer valuable insight to help inform fertility preservation decisions aimed at achieving future live births. This first-of-its-kind systematic review lays the groundwork for future research by identifying key knowledge gaps and emerging areas of clinical relevance.